Identification and prioritization of flood-prone sub-watersheds using morphometric analysis and remote sensing in the Beshilo Sub-basin, Ethiopia - Jemal Ali Mohammed; Zinet Alye Yimam; Solomon Addissu; Adem Endris; Belay Haile; Alemnew Ali; Selemon Tsegaye; Kasye Shitu; Yesuf Mohammed (Geocarto International)
Floods are among the most frequent and damaging natural hazards worldwide, with impacts exacerbated by climate change and unsustainable land use, especially in data-scarce regions. This study assessed flood susceptibility in the Beshilo Sub-basin of Ethiopia using morphometric analysis. Nineteen morphometric parameters were derived from a 12.5 m ALOS PALSAR DEM using ArcMap 10.8.2. Ten sub-watersheds were prioritized based on their Compound Parameter (CP) values, ranging from 4.47 in SW-3 to 6.00 in SW-8. The most flood-prone sub-watersheds were SW-3 (CP = 4.47), SW-7 (4.74), and SW-1 (5.37), while SW-8 (6.00), SW-4 (5.89), and SW-9 (5.89) were the least susceptible. These results suggest that highly vulnerable areas require targeted interventions, including structural measures like terracing and gully stabilization, and non-structural strategies such as improved land-use planning. This method offers a practical, low-cost tool for flood risk assessment and watershed prioritization in similar ungauged basins globally.